A Novel Method for Reducing the Sensitivity Deviation of MEMS Microphones by Programming. (2015) - Walser, S.; Siegel, C.; Winter, M.; Rocca, G.; Leidl, A.; Feiertag, G.
Abstract: This paper describes a novel method for trimming a low noise, differential micro-electromechanical system (MEMS) microphone with a state of the art signal to noise ratio (SNR) of 66 dB(A) and a sensitivity of -38 dBV/Pa @ 1 kHz after completing the fabrication process. The method allows compensating the electroacoustic variations caused by process tolerances and reducing specification limits of the microphone sensitivity from ±3 dB to ±0.5 dB. Trimming is done by programming the bias supply voltage of the capacitive membrane-backplate-system and the gain factor of the output pre-amplifier. Microphone sensitivity can be modified within a range of 11.2 dB. Thus the standard deviation of the sensitivity of a production batch could be reduced from 0.97 dB to 0.11 dB. Furthermore the SNR could be increased to 66.5 dB(A).